A novel task for examining the neural basis of Theory of Mind deficits in bipolar disorder. (30th December 2018) - Grant, Kiran; Hassel, Stefanie; Bobyn, Jacqueline A.; Hall, Geoffrey B.C.; MacQueen, Glenda M.
Highlights: Significant differences in neural activation between HC and BD patients in ToM processing regions. In HC only, correlations between DAS scores and neural activity in medial frontal and cingulate gyri. Increased activation in ToM brain regions in BD shows disrupted networks for social-cognitive processes. Abstract: Deficits in theory of mind (ToM) processing have been observed in people with bipolar disorder (BD), but the neural basis of these deficits remains unclear. Here, we studied the relations between neural activation, dysfunctional beliefs and behavioral responses in people with BD during a second-order ToM task. Twenty-five patients and 25 healthy-control participants (HC) underwent functional magnetic resonance imaging (fMRI) while performing a novel ToM task. The Dysfunctional Attitudes scale (DAS) and the Brief Hypomanic Attitudes and Positive Predictions Inventory (BHAPPI) were used to assess dysfunctional beliefs. Significant differences in neural activation were observed between HC and BD patients in regions associated with ToM processing: medial frontal, cingulate, anterior cingulate and superior temporal gyri. Correlations between DAS scores and neural activity in medial frontal and cingulate gyri were observed for HC only. Increased activation in brain regions associated with ToM processing in patients compared to HC provides further evidence of disruption in networks controlling social-cognitive processes. Whether this results from compensatory responses to maintain appropriate behavior is unknown.